Geographical Indication and Traditional Wisdom: A Study with Special Reference to Chamba Rumal in Himachal Pradesh - Pallathadka, Harikumar; Kumar, Sanjeev; Pallathadka, Laxmi Kirana (Integrated Journal for Research in Arts and Humanities, 2022)
Geographical Indications and traditional knowledge associated with Chamba rumal in the state of Himachal Pradesh are the current research subjects. A visual art form characterized by characteristic embroidery, Chamba Rumal arose and flourished in Chamba, Himachal Pradesh, during the 17th and 18th centuries and is being practiced today. Rumal is a Persian name that refers to a square piece of cloth that is used as a handkerchief in traditional Persian culture. Paintings influence the fundamental structure and themes of Chamba Rumal; there is a prevalence of God depictions, notably of Vishnu in his numerous incarnations, which is a theme that runs throughout the collection of paintings. Dorukha-tanka embroidery is an extremely rare and one-of-a-kind stitch that has never been seen before in the history of Indian embroidery. The Dorukha-tanka stitch is a double satin stitch that is employed in Chamba Rumal embroidery. The present research attempted to determine the degree of public awareness of traditional knowledge connected to GI Chamba rumal in the state of HP. This study also sheds light on the historical context of Chamba rumal and the many topics and traditional knowledge associated with Chamba rumal, among other things.